Characteristics of the environmental information of civil construction companies listed in b3 (Revista Brasileira de Contabilidade e Gestão, 2020)
This study aims to analyze the characteristics of environmental information disclosed by the construction companies listed in B3. In order to carry out the research, Standardized Financial Statements (DFPs), Reference Forms (FR), Annual Reports (RAN) and Sustainability Reports (RS) were analyzed, from 2010 to 2016. To analyze the characteristics of the information environment, a structure divided into nine categories was used, consisting of 38 items, according to the study by Santos (2016). From the content analysis, three classification criteria were defined, which comprise the evidence (declarative, monetary quantitative or quantitative and monetary), the type of news evidenced (good, bad, or neutral) and the location of the information (DFPs, FR, RA and RS). The results obtained in the research show that companies concentrate environmental information, mainly in Reference Forms. With regard to the type of news, it was possible to notice that about 50% of companies choose to publish good news. The bad information comprised 6 of the 18 companies in the study. It was found that most information was disclosed by companies in a declarative manner. These results contribute to the understanding that, as enunciated by the Theories of Legitimacy and Stakeholders, companies, as a way to show their actions, in order to meet the informational demand of their interested parties, and guarantee their legitimacy, evidence information of an environmental nature, even if they are not required by law.
Keywords: Environmental Disclosure; Characteristics of Environmental Information; Construction